Online Gambling Promotion Liability under Indonesian Electronic Information Law: Pertanggungjawaban Pidana Promosi Judi Online Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik - Sheilla Virginia Andreyn; Hery Firmansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital technology and social media have reshaped public interaction while also creating new forms of cybercrime. Specific Background One growing legal issue is the promotion of online gambling websites through social media platforms using links, referrals, endorsements, and disguised digital content. Knowledge Gap Legal uncertainty remains regarding the scope of distributing, transmitting, and making accessible gambling-related electronic information, especially for influencers, affiliates, content creators, and other third parties. Aims This study analyzes the regulation of online gambling website promotion under the Electronic Information and Transactions Law and examines criminal liability for parties involved in disseminating digital gambling content. Results Promotion through social media can be classified as a criminal offense under Article 27 paragraph (2) in conjunction with Article 45 paragraph (3), with liability extending beyond operators to knowing participants. Novelty The study clarifies that digital promotion functions as part of gambling-content dissemination in cyber law. Implications Regulatory strengthening, cyber enforcement optimization, and platform supervision are needed to create safer digital space. Highlights: Disseminating betting content can satisfy distribution, transmission, and accessibility elements. Liability extends to influencers, affiliates, creators, and knowing participants. Anonymous accounts, foreign servers, disguised content, and evidentiary complexity hinder enforcement. Keywords: Online Gambling, Social Media, Cybercrime, Criminal Liability, Electronic Information and Transactions Law.